A new species of Brontostoma Kirkaldy, description of the male of Brontostoma bahiensis Gil-Santana, Costa & Marques and notes on Brontostoma doughertyae Gil-Santana et al. (Hemiptera: Heteroptera: Reduviidae: Ectrichodiinae) - Gil-Santana, Hélcio R. (Zootaxa, 2023)
Brontostoma herczeki sp. nov. is described based on two males from southeastern Brazil (Hemiptera: Heteroptera: Reduviidae: Ectrichodiinae). The male of Brontostoma bahiensis Gil-Santana, Costa & Marques, 2004 is described based on a specimen from Bahia state, Brazil. Taxonomical notes on Brontostoma doughertyae Gil-Santana, Lopes, Marques & Jurberg, 2005 are provided. Photographs of the holotypes of Brontostoma bahiensis, Brontostoma diringshofeni Gil-Santana & Baena, 2009 and Brontostoma doughertyae are presented.